Federation and the History of the Administration of Indigenous Affairs in Canada, the United States, and Australia: New Insights through a Transnational Approach - Binnema, Ted (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
The importance of decisions regarding the allocation of jurisdiction over Indigenous affairs in federal states can only be understood well when studied transnationally and comparatively. Historians of Canada appear never to have considered the significance of the fact that the British North America Act (1867) gave the Canadian federal government exclusive jurisdiction over Indian affairs, even though that stipulation is unique among the constitutional documents of comparable federal states (the United States and Australia). This article explains that the constitutional provisions in Canada, the United States, and Australia are a product of the previous history of indigenous-state relations in each location, but also profoundly affected subsequent developments in each of those countries. Despite stark differences, the similar and parallel developments also hint at trends that influenced all three countries.